2019
DOI: 10.1029/2018jb017135
|View full text |Cite
|
Sign up to set email alerts
|

Offshore Postseismic Deformation of the 2011 Tohoku Earthquake Revisited: Application of an Improved GPS‐Acoustic Positioning Method Considering Horizontal Gradient of Sound Speed Structure

Abstract: One of the important issues on the GPS‐acoustic (GPS‐A) observation for sea bottom positioning is how to address the horizontal heterogeneity of the sound speed in oceans. This study presents an analysis method of GPS‐A data in the presence of a sloping sound speed structure. By applying this method and revising the analysis scheme to make full use of existing data, we reevaluated the horizontal postseismic deformations occurring ~1.5–5 years after the 2011 Tohoku earthquake. The revised horizontal movements h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(115 citation statements)
references
References 53 publications
4
111
0
Order By: Relevance
“…S1). The GNSS-A seafloor geodetic observation greatly constrained the interplate coupling condition (16,17) along the Nankai Trough subduction zone and detected, in detail, postseismic fields along the Japan Trench (18,19). Recently, we improved GNSS-A technology and upgraded the observation sensitivity (20) to detect a transient crustal deformation caused by large interplate slip.…”
Section: Introductionmentioning
confidence: 99%
“…S1). The GNSS-A seafloor geodetic observation greatly constrained the interplate coupling condition (16,17) along the Nankai Trough subduction zone and detected, in detail, postseismic fields along the Japan Trench (18,19). Recently, we improved GNSS-A technology and upgraded the observation sensitivity (20) to detect a transient crustal deformation caused by large interplate slip.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Honsho et al (2019) showed a more general expression for one-dimensional sound speed gradient. As they mentioned, the gradient terms in their formulation correspond to the extracted features in .…”
Section: Recent Improvements On Gnss-a Analytical Proceduresmentioning
confidence: 99%
“…As they mentioned, the gradient terms in their formulation correspond to the extracted features in . The work by Honsho et al (2019) showed the possibility to connect all the GNSS-A configurations into a unified GNSS-A solver. However, due to the limitation in resolving the general gradient structure, an additional constraint was taken for the practical application, which concludes to essentially the same formulation as Yasuda et al (2017).…”
Section: Recent Improvements On Gnss-a Analytical Proceduresmentioning
confidence: 99%
“…The GNSS-A observations enable measurement of seafloor displacements in a global geodetic coordinate system. The system has provided important geodetic observation results including detection of interseismic (e.g., Gagnon et al 2005;Tadokoro et al 2012;Yokota et al 2016), coseismic (e.g., Tadokoro et al 2006;Sato et al 2011;Kido et al 2011), and postseismic (e.g., Watanabe et al 2014;Tomita et al 2015Tomita et al , 2017Honsho et al 2019) deformation associated with earthquake cycles in subduction zones, and plate motions near ridgetransform boundaries (Chadwell and Spiess 2008).…”
Section: Introductionmentioning
confidence: 99%
“…1 Schematic image of the GNSS-Acoustic observation system. Schematic image of a GNSS-A observation system is shown; inclination angle ( ǫ ), shot angle ( ξ ), and azimuth for the seafloor transponder ( φ ) are used in equations in the main text GNSS-A positioning methods that consider the horizontally graded structure of underwater sound speeds that are persistent over the long-term (over several hours) have recently been developed (e.g., Yasuda et al 2017;Yokota et al 2018;Honsho et al 2019), and have demonstrated some reduction in biased positioning errors. However, it has been found that short-term fluctuations in the horizontal heterogeneity of the SSS can be caused by internal gravitational waves (e.g., Spiess et al 1998;Kido et al 2006;Tomita et al 2015), and these short-term fluctuations have degraded the precision of the kinematic GNSS-A positioning method.…”
Section: Introductionmentioning
confidence: 99%